An empirical investigation into urban informal tire repair service in Ilorin, Nigeria (2011)
The employment generation capacity of the formal sector comprising the public and organized private sectors in Nigeria is shrinking. The informal sector therefore offers a ray of hope for employment and earnings for urban unskilled and semi skilled labour. The promotion of informal sector activities by the government requires an insight into their mode of operation for better policy targeting. This paper therefore examines the operational characteristics, financing, training, employment and earnings, and challenges of tire repair business in Ilorin, Nigeria. The data were collected through a structured questionnaire and analyzed using descriptive statistics and phi coefficient. The study finds that tire repair provides employment and income for low skilled labour, most of whom are underemployed, earning about US$7.36 per day. The study finds that age, apprentice access and tire repair service index have significant association with earnings. About 92% of the operators sourced their financing for start-up capital from the informal financial sector. The informal training required is through the apprenticeship scheme, which is largely deficient in safety issues relating to tire rating, maximum load, expiry date, resistance, etc. The safety gap in the apprenticeship training scheme should be bridged through training and seminar. The informal sector support agencies should be overhauled to provide financing, technical and extension services to the informal sector operators.